The Role of the Polish Military Contingent in the Reconstruction of Ghazni Province - Sabawoon, Mirza (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The article outlines the activity of the Polish army as part of NATO operations in Afghanistan. The analysis concerns humanitarian aid in particular, and identifies the most important activities of the PRT (Provincial Reconstruction Team) carried out in the field of reconstruction and security in the city of Ghazni from 2001. The PMC (Polish Military Contingent) worked for the stability of the city, starting in mid-2008. The author concludes that the objectives pursued by the PMC related to the reconstruction of the city of Ghazni increased the level of security of the local community and the overall stability in the region. The methods used in the article (comparative, research, systemic and genetic explanation method) make it possible to examine and present the processes and changes taking place.

Artykuł dotyczy aktywności wojska polskiego w ramach działań NATO w Afganistanie. Analiza w szczególności dotyczy udzielonej pomocy humanitarnej oraz wskazania na najważniejsze działania prowadzone od 2001 r. w sprawie działalności PRT (Zespół Odbudowy Prowincji) w kwestii odbudowy, bezpieczeństwa miasta Ghazni. Od połowy 2008 r. PKW (Polski Kontyngent Wojskowy) działał na rzecz stabilizacji wskazanego miasta. Autor przedstawia wniosek, że realizowane przez PKW cele związane z rekonstrukcją miasta Ghazni przyczyniły się do podniesienia poziomu bezpieczeństwa lokalnej społeczności oraz ogólnej stabilizacji w regionie. Wykorzystane w artykule metody (porównawcza, badawcza, systemowa czy wyjaśnienia genetycznego) umożliwią zbadanie i przedstawienie zachodzących procesów i zmian.
Rola PKW w odbudowie prowincji Ghazni
Keywords: PMC (Polish Military Contingent); Afghanistan; Ghazni; mission; stability; security; peace; PRT (Provincial Reconstruction Team); PKW (Polski Kontyngent Wojskowy); Afganistan; Ghazni; misja; stabilizacja; bezpieczeństwo; pokój; PRT (Zespół Odbudowy Prowincji)